Village’s Strategic in Facing Potential Fraud on Sistem Keuangan Desa (Siskeudes) - Audela, Kezya; Hadiluwarso, Felicia A; Kristianti, Ika (Universitas Pamulang, 2022)
This study will identify the village's ability to deal with potential fraud in the management of the village financial system. An increase in the allocation of village funds that is not followed by progress and good village financial management can increase fraud. In response to this, the Government facilitate internal control related to the management of village funds through SISKEUDES. Therefore, it is necessary to see Village X’s SISKEUDES management during Covid-19 pandemic, where economic conditions in Indonesia weakened. In Covid-19 pandemic, The Government has increased the amount of village fund allocations so that the opportunity to commit fraud during economic pressure experienced by the community is increasingly wide open. The research was conducted in Village X using a qualitative descriptive method. The data was obtained through the process of interview with village heads, treasurers. Analysis tech-nique used is data triangulation. The results of the study state that the possibility of fraud in Village X is quite significant because SISKEUDES can be accessed by all village officials, no regular change of username and password, no supervision in document input, the low educational background of the majority of Village X residents. In addition, research also shows that increasing village fund allocations are not in line with progress and good fund management. This research can be a evaluation and a reference in developing existing regulations to improve defense capabilities in managing the village financial system also can be helpful for related agencies, as the development of internal control for optimal system management.